Validation of an Oral Disease Severity Score (ODSS) tool for use in oral mucous membrane pemphigoid. (1st July 2020) - Ormond, M.; McParland, H.; Thakrar, P.; Donaldson, A.N.A.; Andiappan, M.; Cook, R.J.; Escudier, M.E.; Higham, J.; Hullah, E.; McMillan, R.; Taylor, J.; Shirlaw, P.J.; et al.
Summary: Background: Mucous membrane pemphigoid (MMP) is a rare autoimmune bullous disease predominantly affecting the oral mucosa. Optimal management relies upon thorough clinical assessment and documentation at each visit. Objectives: The primary aim of this study was to validate the Oral Disease Severity Score (ODSS) for the assessment of oral involvement in MMP. We also compared its inter‐ and intraobserver reliability with those of the oral parts of the Mucous Membrane Pemphigoid Disease Area Index (MMPDAI), Autoimmune Bullous Skin Disorder Intensity Score (ABSIS) and Physician's Global Assessment (PGA). Methods: Fifteen patients with mild‐to‐moderately severe oral MMP were scored for disease severity by 10 oral medicine clinicians from four U.K. centres using the ODSS, the oral sections of MMPDAI and ABSIS, and PGA. Two clinicians rescored all patients after 2 h. Results: In terms of reliability, the interobserver ODSS total score intraclass correlation coefficient (ICC) was 0·97, MMPDAI activity 0·59 and damage 0·15, ABSIS total 0·84, and PGA 0·72. The intraobserver ICCs (two observers) for ODSS total were 0·97 and 0·93; for MMPDAI activity 0·93 and 0·70 and damage 0·93 and 0·79; for ABSIS total 0·99 and 0·94; and for PGA 0·92 and 0·94. Convergent validity between ODSS and MMPDAI was good (correlation coefficient 0·88). The mean ± SD time for completion of ODSS was 93 ± 31 s, with MMPDAI 102 ± 24 s and ABSIS involvement 71 ± 18 s. The PGA took < 5 s. Conclusions: This study has validated the ODSS for the assessment of oral MMP. It has shown superior interobserver agreement over MMPDAI, ABSIS and PGA, and superior intraobserver reliability to MMPDAI. It is quick and easy to perform. What's already known about this topic? There are no validated scoring methodologies for oral mucous membrane pemphigoid (MMP). Proposed disease activity scoring tools for MMP include the Mucous Membrane Disease Area Index (MMPDAI) and the Autoimmune Bullous Skin Disorder Intensity Score (ABSIS). The Oral Disease Severity Score (ODSS) has been validated for use in oral pemphigus vulgaris (PV). It has been shown to be reliable and sensitive in both lichen planus (LP) and MMP. What does this study add? The ODSS has been shown to be a thorough, sensitive and reproducible, yet quick scoring tool for the assessment of oral involvement in MMP. Its versatility for use in oral PV, MMP and LP is an added advantage over other scoring methodologies. What are the clinical implications of this work? We propose that the ODSS be used as a clinical scoring tool for monitoring activity in oral MMP in clinical practice as well as for use in multicentre studies.